Core-size dispersity dominates the self-assembly of polymer grafted nanoparticles in solution - Bachhar, Nirmalya; Kurnaraswamy, Guruswamy; Kumar, Sanat K. (Macromolecules, 2019)
In polymer-grafted nanoparticles (PGN), covalent tethering of apolar polymer chains to a polar inorganic nanoparticle core induces the formation of self-assembled aggregates. Since the nature of these aggregates determines bulk mechanical and transport properties, it is of importance to understand the factors that determine the underlying assembly processes. In the literature, the solution assembly of PGNs has been understood in analogy to small-molecule amphiphiles. However, in any experimental realization, PGNs are invariably characterized by additional structural complexity, such as the distributions in the inorganic core size and in the grafted chains (both in their length and grafting density). These strongly influence the assembly of amphiphilic PGNs. We have previously demonstrated that dispersity in core size qualitatively affects the structure of PGN aggregates, and Jayaraman et al. demonstrated the effect of grafted chain-length dispersity. The combined effects of dispersity in the size of the core and grafted chains have not been explored previously. Here, we develop a model that builds on the work of Daoud and Cotton to explore a wide parameter space of PGN with dispersity simultaneously in core size and grafted chain length. We demonstrate that dispersity in core size is the dominant factor affecting the self-assembled solution structure of PGN aggregates. Our work suggests the importance of focusing on synthetic strategies for control of core-size dispersity to control aggregate structure in PGN.